HEMA based pH-sensitive semi IPN microgels for oral delivery; a rationale approach for ketoprofen. (1st February 2020) - Zia, Muhammad Adnan; Sohail, Muhammad; Minhas, Muhammad Usman; Sarfraz, Rai Muhammad; Khan, Shahzeb; de Matas, Marcel; Hussain, Zahid; Abbasi, Mudassir; Shah, Syed Ahmed; Kousar, Mubeen; Ahmad, Naveed
Abstract: Objectives: The study aimed to develop safe, effective, and targeted drug delivery system for administration of nonsteroidal anti-inflammatory drugs (NSAIDs) in the form of microgels. We developed pH responsive microgels to overcome the mucosal damage caused by traditional immediate release dosage forms. Colon targeting and controlled release formulations have the potential to improve efficacy and reduce undesirable effects associated with NSAIDs. Methods: The pH sensitive oral hydrogel demonstrates the potential to target the colon. Cellulose acetate phthalate (CAP) and hydroxyethyl methacrylate (HEMA) based microgel particles were produced using a free radical polymerization technique using ammonium persulfate (APS) initiator and methylenebisacrylamide (MBA) as the crosslinking agent. Swelling and in-vitro drug release studies were performed at a range of pH conditions. The produced formulations were characterized using Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, scanning electron microscopy (SEM), and X-ray diffraction. Biocompatibility of the microgels was analyzed in cytotoxicity studies. Key findings: The swelling and release rate were negligible at pH 1.2, which confirmed the pH-responsiveness of CAP- co -poly(HEMA). The co-polymeric system prevents the release of ketoprofen sodium in the stomach owing to limited swelling at gastric pH, whilst promoting release at the basic pH observed in the colon. SEM images confirmed porous nature of the microgels that facilitate effective drug diffusion through the polymeric matrix. Cytotoxicity studies revealed biocompatibility of hydrogels. Conclusion: These investigations showed that that the controlled drug release and gastro-protective drug delivery of NSAIDS was achieved using CAP- co -poly(HEMA) microgel particles.